2016
DOI: 10.1246/cl.160261
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureusDetection by Fluorescent Silica Nanoparticles Modified with Metal–Dipicolylamine Complexes

Abstract: We have developed a new method for Staphylococcus aureus (S. aureus) detection, which employs fluorescent silica nanoparticles (FSiNPs) modified with metaldipicolylamine complex (M-dpa-HCC). Among the M-dpa-HCC/FSiNP complexes, Cu-dpa-HCC/FSiNP formed large aggregates with S. aureus in 10 min, which were easily observed by the naked eye. The antibacterial activity of Cu-dpa-HCC/FSiNP was also confirmed. 46 However, the culture method requires nearly five days for detection, whereas the other two methods are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…In the same manner as many biological challenges [ 16 , 17 ], nanoprobes with binding sites as a recognitive function represent a potential solution. For instance, nanoprobes with dipicolylamine for Staphylococcus aureus [ 18 ] or Escherichia coli [ 19 , 20 ], mannose towards E. coli [ 21 , 22 ], cationic amine groups [ 23 , 24 ] and vancomycin [ 25 ] for various species, or cell wall binding domains for corresponding bacteria [ 26 ] were developed to attempt instant and sensitive detection of bacteria. Many laboratories have focused on bacteria detection by convenient optical measurements, such as luminescence changing [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the same manner as many biological challenges [ 16 , 17 ], nanoprobes with binding sites as a recognitive function represent a potential solution. For instance, nanoprobes with dipicolylamine for Staphylococcus aureus [ 18 ] or Escherichia coli [ 19 , 20 ], mannose towards E. coli [ 21 , 22 ], cationic amine groups [ 23 , 24 ] and vancomycin [ 25 ] for various species, or cell wall binding domains for corresponding bacteria [ 26 ] were developed to attempt instant and sensitive detection of bacteria. Many laboratories have focused on bacteria detection by convenient optical measurements, such as luminescence changing [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported on fluorescent silica nanoparticles (FSiNPs) modified with M (metal ion)-dpa-HCC for S. aureus detection. 24 The M-dpa-HCC/FSiNP complex efficiently formed aggregates with S. aureus. In that study, we observed interesting responses towards metal ions and phosphate anions as well.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we reported fluorescent silica nanoparticles (FSiNPs) modified with metaldipicolylamine complex (M-dpa-HCC) for Staphylococcus aureus (S. aureus) detection. 23) Among the M-dpa-HCC/FSiNP complexes, Cu-dpa-HCC/FSiNP formed large aggregates with S. aureus in 10 min, which were easily observed by the naked eye. Herein, we develop two types of fluorescent silica nanoparticles (FSiNP) and evaluate bacteria recognition function (Scheme 1).…”
mentioning
confidence: 95%